The Value of Age-Friendly Public Health Systems in the Age-Friendly Ecosystem - Megan Wolfe; J. Nadine Gracia (Geriatrics, 2023)
The United States population is living longer and healthier than ever. This enables our communities—and our society—to continue to benefit from our knowledge, experience, and energy as we age. The public health system is foundational for increasing life expectancy, and now it has the opportunity to further support older adult health and well-being. Trust for America’s Health (TFAH), in partnership with The John A. Hartford Foundation, launched the age-friendly public health systems initiative in 2017 with the goal of raising awareness within the public health sector of its many potential roles in healthy aging. TFAH has worked with state and local departments of health to build capacity and expertise in older adult health and has provided guidance and technical assistance to expand this work across the U.S. TFAH now envisions a public health system that has healthy aging as a core function. This paper aims to describe why the public health sector should adopt healthy aging policies and practices, how this is being operationalized at the state and local levels, and the value of age-friendly public health systems within the age-friendly ecosystem.